Inhibitory Effects of Glycyrrhetinic Acid on the Delayed Rectifier Potassium Current in Guinea Pig Ventricular Myocytes and HERG Channel. (29th August 2013) - Wu, Delin; Jiang, Linqing; Wu, Hongjin; Wang, Shengqi; Zheng, Sidao; Yang, Jiyuan; Liu, Yuna; Ren, Jianxun; Chen, Xianbing
Abstract : Background . Licorice has long been used to treat many ailments including cardiovascular disorders in China. Recent studies have shown that the cardiac actions of licorice can be attributed to its active component, glycyrrhetinic acid (GA). However, the mechanism of action remains poorly understood. Aim . The effects of GA on the delayed rectifier potassium current (I K ), the rapidly activating (I K r ) and slowly activating (I K s ) components of I K, and the HERG K + channel expressed in HEK-293 cells were investigated. Materials and Methods . Single ventricular myocytes were isolated from guinea pig myocardium using enzymolysis. The wild type HERG gene was stably expressed in HEK293 cells. Whole-cell patch clamping was used to record I K (I K r, I K s ) and the HERG K + current. Results . GA (1, 5, and 10 μ M) inhibited I K (I K r, I K s ) and the HERG K + current in a concentration-dependent manner. Conclusion . GA significantly inhibited the potassium currents in a dose- and voltage-dependent manner, suggesting that it exerts its antiarrhythmic action through the prolongation of APD and ERP owing to the inhibition of I K (I K r, I K s ) and HERG K + channel.